ANALISIS SWOT UNTUK PENGEMBANGAN STRATEGI PEMASARAN PRODUK OLAHAN APEL DI MALANG RAYA - Rahayu Relawati; Istis Baroh; Bambang Yudi Ariadi (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
This  study  aimed  to  carry  out  a  SWOT  analysis  and  formulate  marketing strategies  of  processed  apple  products.  Primary  data  were  obtained  from  producers and  consumers.  Producers  were  selected  purposively,  while  consumers  were selected by  accidental  sampling  when  they  bought the  product  at  souvenirs  shops  of Malang. SWOT analysis was used to analyze the data taken from both producers and consumers, as  well  as  to  formulate  marketing  strategies.  The  results  showed  that  in  general  the products of apple chips, porridge and cider have the strength on products, especially in terms  of  taste.  Meanwhile,  the  weaknesses  are  less  durable  products,  however, consumers also do not want any preservatives  added.  Moreover, the opportunities  are the high interest of consumers, many souvenir shops and bank credit offered.  On the other  side,  the  threats  consists  of  unhealthy  business  competition  and  weakness  of consumer purchasing power even though they are interested  in the products. Based on the results of the SWOT  analysis, marketing strategies recommended to  the products  of apple  chips  and  apple  porridge  is  aggressive  strategy,  because  they  are  in  the  first quadrant  of SWOT  diagram.  Apple cider, however,  is  recommended to run a defensive strategy, because this product  is located  in quadrant III  of  the same diagram. Related promotions, various media information such as local television and  internet should be used optimally to promote the  products. Consumers should receive the correct and fare information, so that producers must conduct a responsible business ethics.